2019
DOI: 10.3846/jcem.2019.7642
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of Co-Worker Support on Construction Safety Performance From the Perspective of Risk Theory: An Agent-Based Modeling Approach

Abstract: Co-worker safety support has been given prominence in manufacturing and transportation field for its positive effect on individual workers’ safety; however, there is little evidence to show if such supporting role of co-workers is significant in improving project-level safety performance in construction workplace. This study adopts agent-based modeling (ABM) to understand the effectiveness of two distinct co-worker-safety-support actions on the safety performance of a construction project. Based on the risk th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
9

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
0
7
0
9
Order By: Relevance
“…Observa-se uma distribuição relativamente equilibrada de modelos empíricos e teóricos, sendo a maioria (9 pesquisas) composta por modelos teóricos. Com relação as plataformas de software, observa-se que o software NetLogo se destaca, sendo utilizado por cinco artigos, dois modelos teóricos (A1 [21] e A9 [5]), dois empíricos (A11 [3] e A13 [19]) e um modelo teórico e empírico (A2 [22]). NetLogo, em especial, tem grande presença na comunidade acadêmica por se tratar de uma plataforma de software livre para modelagem baseada em agentes de fácil programação.…”
Section: Análise Dos Resultadosunclassified
See 1 more Smart Citation
“…Observa-se uma distribuição relativamente equilibrada de modelos empíricos e teóricos, sendo a maioria (9 pesquisas) composta por modelos teóricos. Com relação as plataformas de software, observa-se que o software NetLogo se destaca, sendo utilizado por cinco artigos, dois modelos teóricos (A1 [21] e A9 [5]), dois empíricos (A11 [3] e A13 [19]) e um modelo teórico e empírico (A2 [22]). NetLogo, em especial, tem grande presença na comunidade acadêmica por se tratar de uma plataforma de software livre para modelagem baseada em agentes de fácil programação.…”
Section: Análise Dos Resultadosunclassified
“…A modelagem baseada em agentes (ou sua sigla em inglês ABM, Agent based Model) se destaca como uma solução para o desenvolvimento de tais questões. Trabalhos recentes têm buscado analisar o tema a partir desta abordagem bottom up, abordagem esta que analisa os aspectos a partir da base da produção (colaboradores) para o topo (gerência) [3] [4] [5] [6].…”
Section: Introductionunclassified
“…The results of that study led to the suggestions that management teams should emphasise and cultivate the leadership role among supervisors and that senior managers should regularly be involved in safety activities. Ji et al (2019) simulated workers at a construction site with a crane hazard, and the results indicated that combined coworker support actions, such as warning coworkers to leave hazardous areas and reminding them to wear personal protective equipment, could effectively reduce the severity of recordable, lost-time and fatal incidents, whereas a single measure would be more likely to work when nonfatal incidents occurred.…”
Section: Mas Applications In Construction Managementmentioning
confidence: 99%
“…Zhang et al [26] established a model of scaffolding workers' unsafe behaviors and explored the impact of management measures on workers' safety performance. Ji et al [63] adopted the ABM method to simulate the scene of reinforcing steel bars on…”
Section: Agent-based Modelingmentioning
confidence: 99%
“…Zhang et al [26] established a model of scaffolding workers' unsafe behaviors and explored the impact of management measures on workers' safety performance. Ji et al [63] adopted the ABM method to simulate the scene of reinforcing steel bars on the construction site, and proposed the support of the workers can reduce the occurrence of the nonfatal incidents. Liang et al [42] developed a hybrid simulation approach that integrated System Dynamics (SD) and ABM to study the social contagion effect of safety violations within a construction crew.…”
Section: Agent-based Modelingmentioning
confidence: 99%